Ultrasound imaging of the perithyroid fascial space: a comparative analysis with anatomical correlations - Ying Wei; Zhen-long Zhao; Yun Niu; Li-li Peng; Yan Li; Ming-an Yu (Scientific Reports)
Abstract This study aims to examine the ultrasonic characteristics of perithyroid fascial spaces following in vivo hydrodissection, validating their visualization through a comparative analysis with anatomical references. A retrospective review was conducted on data from 2390 patients (631 males and 1759 females, median age 46 years, 25–75% interquartile range 26–69 years) who underwent microwave ablation for thyroid tumors, including 1436 benign nodules and 954 papillary thyroid carcinomas. Detailed descriptions of perithyroid fascial spaces and the hydrodissection strategy were provided. Ultrasonic characteristics of fascial spaces during hydrodissection were documented and systematically compared with anatomical references. Hydrodissection was successfully performed in all cases according to the protocol. Isolating fluid was injected into classic anatomical spaces: anterior cervical (58.5%), pretracheal (71.8%, including Berry’s ligament in 196 cases), retropharyngeal (43.7%), and carotid (1.2%). Additionally, US revealed two new spaces—perilymphatic (4.1%) and tracheoesophageal groove (3.7%)—with corresponding anatomical structures. The US-identified fascial structures aligned with their anatomical positions and distribution. US-guided hydrodissection facilitates the visualization of the fascial space, making it possible to study the microenvironment physiology and pathology of fascia in vivo.